STUDENT’S PERCEPTIONS OF THE USE OF GOOGLE MEET DURING THE LIMITED FACE-TO-FACE LEARNING PERIOD - Al Halim, M. Labib (Universitas Islam Lamongan, 2023)
This research aims to describe student’s perceptions of the use Google Meet during the limited face-to-face learning period at English Education Study Program University of Billfath. This research employed descriptive quantitative research techniques in the form of surveys. An online questionnaire created with Google Forms was used as the research instrument. The result of student’s answer through the questionnaire given showed good category. There were 60% of students strongly agree with the statement that Google was easily accessible, 52% of students strongly agree with the use of Google Meet, they could still understand the material given during lectures, 44% of students strongly agree that the use of google meet during online learning was effective, and 40% of students were highly motivated to participate in learning by using google meet. Thus, it could be concluded that online learning using Google Meet during the limited face-to-face learning period was quite good and effective.